Concrete characteristics using aggregate from Nanga Jemah Village, Kapuas Hulu District for rabat beton road - Rasiwan, Rasiwan; Syahrani, Deny; Supardi, Iwan; Rabihati, Etty; Abduh, Muhammad; Haryani, Susi (International research journal of engineering, IT and scientific research, 2022)
The use of concrete for various building constructions has been widely used, both as a building structure and also for transportation purposes, especially for concrete roads. Nanga Jemah Village is one of the villages located in Boyan District, Kapuas Hulu Regency which has potential in the field of building materials. The use of aggregates originating from Nanga Jemah has often been done, but until now no one has investigated this type of aggregate as a concrete-forming material, especially for the manufacture of concrete rebate roads. The aggregates used in this study are aggregates derived from Nanga Jemah, both fine aggregates and coarse aggregates by comparing the use of commonly used materials. The purpose and objective of this research are to develop the potential of the area in the form of materials originating from the village of Nanga Jemah so that they can be used as concrete-forming materials, especially for the construction of the Rabat Beton road.